Impact of Inventory Management in Paper Industries: Impact of Cheaper Imports on the Indian Paper Industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The domestic paper industry today urged the government to immediately curb cheaper import from ASEAN countries by imposing 10-15 per cent safeguard duty. The industry also demanded that the government should impose 10 percent special additional customs duty on overseas purchase of paper and paperboard. At present, imports of paper and paperboard attract 10 percent customs duty. It has been brought to zero level to ASEAN countries under the free trade agreement and recently duty-free shipments have been permitted from Korea. There is a surge in imports from ASEAN countries, especially from Thailand at zero duty. This is affecting domestic players and we have asked government to impose a safeguard duty of 10-15 percent. Indian paper manufacturing Association (IPMA) and vice chairman of Kolkata based West coast paper mills, said restricting imports are necessary as the domestic paper industry “struggling to sustain because of high cost of raw material, especially of wood.” The production cost is very high in India when compared with other countries because of high cost of wood.